The scapho-capitate syndrome: a case report with follow-up of three years - Pedrazzini, Alessio; Daci, Lisiana; Bertoni, Nicola; Pedrabissi, Bianca; Yewo Simo, Henry; Medina, Vanni; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2019)
The scapho-capitate or Fenton syndrome is characterized by an associate fracture of the scaphoid and capitate with rotation of 90° or 180° of the capitate’s head. We report a case of this syndrome which occurred in a fifteen years old professional motorcyclist who came to our observation following a high-energy trauma that occurred during the track tests. Through a dorsal access the fractures of the capitate and scaphoid were reduced and stabilized with Kirschner wires. The patient was radiographically and clinically evaluated three years after surgery; complete healing of scaphoid fracture and reabsorption of the capitate’s head as consequence of avascular necrosis with the onset of a midcarpal arthritis were observed. Despite this radiographic evolution, the patient achieved excellent clinical result featured by complete recovery of wrist motion and absence of pain thus allowing the return to motorcycling.